The Investment Climate and Enterprise Performance in Rural Pakistan : Implications for Rural Non-farm Employment Generation - Sur, Mona; Zhang, Jian; Chen, Kevin (Taylor and Francis, 2014)
This paper provides a descriptive analysis of the profile of village and small-town enterprises in Pakistan drawing on a large-scale survey of enterprises. Although the enterprise sector does not appear to be particularly dynamic, the data indicate that there has been employment growth in this sector. The average annual compound employment growth has been about 1% in village enterprises and 3% in small-town enterprises. Access to formal finance, the cost of finance and cumbersome loan procedures pose major challenges for rural entrepreneurs in Pakistan, particularly in terms of availing of long-term financing for investment purposes. Access to and quality of electricity supply, marketing difficulties and transportation-related problems also pose major obstacles. These obstacles have a negative impact on enterprise productivity and the level of investments made by existing firms and discourage the start-up of new enterprises. Addressing the constraints faced by non-farm business in villages and small towns is needed to promote private investments, generate employment and reduce poverty.